2012
DOI: 10.1124/mol.112.080788
|View full text |Cite
|
Sign up to set email alerts
|

Requirement of Apoptotic Protease-Activating Factor-1 for Bortezomib-Induced Apoptosis but Not for Fas-Mediated Apoptosis in Human Leukemic Cells

Abstract: Bortezomib is a highly selective inhibitor of the 26S proteasome and has been approved for clinical use in the treatment of relapsing and refractory multiple myeloma and mantle cell lymphoma. Clinical trials are also underway to assess the role of bortezomib in several other human malignancies, including leukemia. However, the mechanism(s) by which bortezomib acts remain to be fully understood. Here, we studied the molecular requirements of bortezomib-induced apoptosis using the human T-cell leukemic Jurkat ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 49 publications
1
7
0
Order By: Relevance
“…For instance, the LP-1 cell line was found to be resistant to bortezomib in our present study (Figure 3). A previous study suggested that the expression of Apaf-1 might be predictive of the response to proteasome inhibition [29]. Based on our present results, patients with MM mimicking the molecular profile/behavior of LP-1 at any clinical evaluation point during the long-term clinical course of MM will be candidates for therapeutic regimens other than bortezomib.…”
Section: Discussionsupporting
confidence: 60%
“…For instance, the LP-1 cell line was found to be resistant to bortezomib in our present study (Figure 3). A previous study suggested that the expression of Apaf-1 might be predictive of the response to proteasome inhibition [29]. Based on our present results, patients with MM mimicking the molecular profile/behavior of LP-1 at any clinical evaluation point during the long-term clinical course of MM will be candidates for therapeutic regimens other than bortezomib.…”
Section: Discussionsupporting
confidence: 60%
“…7 a, b). We also performed western blot for polyubiquitinated proteins as described previously [ 45 ], and we could detect an accumulation of polyubiquitinated proteins in cells exposed to a BMD 20 dose (25 µg/mL) of CuO NPs (Fig. 6 c).…”
Section: Resultsmentioning
confidence: 98%
“…Their mechanism of action involves inhibition of the proteasome which affects critical pathways for cellular survival through nuclear factor Kβ signaling, Jun N-terminal kinase (JNK) pathway, histone deacetylase action and suppression of anti-apoptotic proteins [Mujtaba and Dou, 2011; Dou and Zonder, 2014]. Other studies using cell lines derived from T-ALL indicated that expression of Apaf-1 has an important role in bortezomib-induced apoptosis [Ottosson-Wadlund et al 2013]. The Nalm-6 cell line [Adachi et al 2006] recapitulates aspects of B-ALL biology and in vitro experiments using bortezomib highlighted an array of antileukemic mechanisms.…”
Section: Kinase Targeting Therapies and Immunomodulatory Agentsmentioning
confidence: 99%